Improvement in blastocyst quality by neurotensin signaling via its receptors in bovine spermatozoa during in vitro fertilization - Kohei UMEZU; Risa YAJIMA; Yuuki HIRADATE; Rin YANAI; Takashi NUMABE; Kenshiro HARA; Toshinori OIKAWA; Kentaro TANEMURA (The Journal of Reproduction and Development, 2019)
Previously, we reported that neurotensin (NT), which is expressed in the uterus and oviduct, enhanced bovine sperm capacitation and acrosome reactions. As NT mRNA expression in bovine oviducts increases dramatically in the follicular phase, we hypothesized that NT modulates fertilization and subsequent conception in cattle. The objective of this study was to evaluate the effect of NT on embryo development and blastocyst quality. The rate of embryo cleavage was significantly increased by the addition of NT to the fertilization medium. Furthermore, the total number of cells and numbers of cells in the inner cell mass of blastocysts were significantly increased by NT during in vitro fertilization (IVF). These results suggested that NT enhanced the efficiency of early bovine embryo development and blastocyst quality. The expression of NT receptors (NTRs) in sperm, testes, oocytes, and cumulus cells was evaluated to determine whether NT acted via NTRs in sperm alone or in both male and female reproductive cells during IVF. Immunocytochemistry and reverse transcription polymerase chain reaction revealed that NTR1 and NTR2 were expressed in sperm and testes, but not in oocytes and cumulus cells. We propose that NT selectively acts upon sperm via NTR1 and NTR2 during IVF to improve the cleavage rate and quality of blastocysts, which are important determinants of sperm quality for successful conception. This research supports our hypothesis that NT acts as a key modulator of fertilization and conception in cattle. Further studies are necessary to apply our findings to the industrial framework of bovine reproduction.